Sociedade civil global e a construção dos direitos humanos - Barros Filho, Mario Thadeu Leme de (2008)
This thesis aims to analyze the role of the global civil society before the international institutions for the construction of the human rights, comprehended as intercultural. It will defend that, in the legal pluralistic universe, the human rights must be conceived by an intercultural paradigm, in order to overcome the debate about cultural universalism vs. relativism. Firstly, it aims to understand how a new theory of law, which allows the participation of new actors in the global scenario, can present itself as counter-hegemonic. Then, it will try to observe in which moment and in which political context the concept of global civil society starts to appear more frequently, with a view of identifying the historical conditions that enabled the creation and reproduction of different speeches on it. Finally, after having presented the thesis on interculturalism, it will highlight the relevant aspects connected to the participation of the civil society before the United Nations, bringing the empirical experience of the Committee on the Elimination of all Forms of Discrimination against Women